Aplicación móvil de localización y ubicación de las dependencias para personas que ingresen en la Universidad Técnica de Cotopaxi la matriz Latacunga - Cajas Torres, Dennis Paul (2016)
This project involves a mobile application development on Android operating system. This is a support the orientation and location services and units for people who enter at Cotopaxi Technical University on structural and human environment around him. For this action QR codes and a video system are applied in order to locate the dependence. A MOBIL-D methodology is used for application creation. This application is able to provide information from different departments which are there in the university such as: dependency names, the stuff’s names, working hours, URL dependence, and dependence description. The first step to provide the information is QR codes Reading. It has all information on each site within the university. These are located at a specific point for easy access to users. The project allows interested persons who go to college, get direct information on facilities, services and premises of the institution, and thus avoid the waste of time for the purposes they want to know.